Cellular and molecular crosstalk between leptin receptor and estrogen receptor-α in breast cancer: molecular basis for a novel therapeutic setting - Roberta Fusco; Mario Galgani; Claudio Procaccini; Renato Franco; Giuseppe Pirozzi; Laura Fucci; Paolo Laccetti; Giuseppe Matarese (2010)
Obesity is associated with an increased risk of breast cancer. A number of adipocytokines are increased in obesity causing low-level chronic inflammation associated with an increased risk of tumors. The adipocytokine leptin shows profound anti-obesity and pro-inflammatory activities. We have hypothesized that in common obesity, high circulating leptin levels might contribute to an increased risk of breast cancer by affecting mammary cell proliferation and survival. Leptin exerts its activity not only through leptin receptor (LepR), but also through crosstalk with other signaling systems implicated in tumorigenesis. In this study, we focused our attention on the relationship between the leptin/LepR axis and the estrogen receptor-alpha (ERalpha). To this aim, we utilized two human breast cancer cell lines, one ERalpha-positive cell line (MCF 7) and the other ERalpha-negative cell line (MDA-MB 231). We observed that the two cell lines had a different sensitivity to recombinant leptin (rleptin): on MCF 7 cells, rleptin induced a strong phosphorylation of the signal transducer and activator of transcription (STAT) 3 and of the extracellular related kinase 1/2 pathways with an increased cell viability and proliferation associated with an increased expression of ERalpha receptor. This response was not present in the MDA-MB 231 cells. The effects induced by leptin were lost when LepR was neutralized using either a monoclonal inhibitory antibody to LepR or LepR gene-silencing siRNA. These data suggest that there is a bidirectional communication between LepR and ERalpha, and that neutralization and/or inactivation of LepR inhibits proliferation and viability of human breast cancer cell lines. This evidence was confirmed by ex vivo studies, in which we analyzed 33 patients with breast cancer at different stages of disease, and observed that there was a statistically significant correlation between the expression of LepR and ERalpha. In conclusion, this study suggests a crosstalk between LepR and ERalpha, and could envisage novel therapeutic settings aimed at targeting the LepR in breast cancers.